Bi-directional relations between stress and self-reported and actigraphy-assessed sleep: a daily intensive longitudinal study. Issue 3 (14th October 2019) - Yap, Yang; Slavish, Danica C; Taylor, Daniel J; Bei, Bei; Wiley, Joshua F
Abstract: Study Objectives: Stress is associated with poor and short sleep, but the temporal order of these variables remains unclear. This study examined the temporal and bi-directional associations between stress and sleep and explored the moderating role of baseline sleep complaints, using daily, intensive longitudinal designs. Methods: Participants were 326 young adults ( M age = 23.24 ± 5.46), providing >2, 500 nights of sleep altogether. Prospective total sleep time (TST), sleep onset latency (SOL), wake after sleep onset (WASO), and sleep efficiency (SE) were measured using actigraphy and sleep diaries. Perceived stress was reported three times daily between: 11:00–15:00, 15:30–19:30, and 20:00–02:00. Sleep complaints were measured at baseline using the PROMIS sleep disturbance scale. Within- and between-person sleep and stress variables were tested using cross-lagged multilevel models. Results: Controlling for covariates and lagged outcomes, within-person effects showed that higher evening stress predicted shorter actigraphic and self-reported TST (both p < .01). Conversely, shorter actigraphic and self-reported TST predicted higher next-day stress (both p < .001). Longer self-reported SOL and WASO (both p < .001), as well as lower actigraphic ( p < .01) and self-reported SE ( p < .001), predicted higher next-day stress. Between-person effects emerged only for self-reported TST predicting stress ( p < .01). No significant results were found for the moderating role of baseline sleep complaints. Conclusions: Results demonstrated bi-directional relations between stress and sleep quantity, and a consistent direction of worse sleep quantity and continuity predicting higher next-day stress. Results highlighted within-individual daily variation as being more important than between-individual differences when examining sleep and daytime functioning associations.